The Effect of Internal Control System, Information Asymmetry, and Suitability of Compensation on the Tendency of Accounting Fraud (Fraud) in Denpasar City (Opd) - DEWI, Ririn Oktavia Citra; SAPUTRA, Komang Adi Kurniawan; PRAMARTHA, I Made Aditya (Journal of Governance, Taxation and Auditing, 2024)
This research aims to determine the influence of internal control systems, information asymmetry, and suitability of compensation on the tendency of accounting fraud in regional organizations in Denpasar City. The population used in this research was 21 Regional Apparatus Organizations in Denpasar City using a saturated sampling technique. The respondents used in this research were 42 respondents. This research uses several data analysis techniques. The data analysis techniques used in this research are the Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Analysis (Adjusted R Square), F Test, and t-test. Based on the results of the analysis that has been carried out, it can be seen that the results of this research are that the Internal Control System has a significant negative effect, Information Asymmetry has a significant positive effect, and Compensation Suitability has a significant negative effect. Its Influence on Accounting Fraud Tendencies in Denpasar City Regional Organizations.